Das Äthiopien in Adolph Knigges Roman: Realität oder Hilfsmittel - Six, Veronika (Aethiopica, 1999)
The German Adolph Knigge (1752–96), an exponent of the Age of Enlightenment, is the author of a novel, which he gave a title including some Ethiopian elements. This article seeks to answer three questions: 1. How far the description of Knigge’s Ethiopia does agree with the “real” Ethiopia. 2. What could have been the sources of his information and knowledge. 3. Why did he choose Ethiopia as peg, though he was not writing for Ethiopianists or people alike. It is obvious that for the description of the fictitious Ethiopian novel Knigge took the information from Bruce’s travel report. And it is obvious that he was familiar with Ludolf and his time. Knigge being interested in a success of his publications could rely on a sales promoting effect of the book title because of the background of information of his 18th century readership.